2012
DOI: 10.1016/j.bbr.2012.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between modafinil and cocaine during the induction of conditioned place preference and locomotor sensitization in mice: Implications for addiction

Abstract: Modafinil is a wake-promoting drug effective at enhancing alertness and attention with a variety of approved and off-label applications. The mechanism of modafinil is not well understood but initial studies indicated a limited abuse potential. A number of recent publications, however, have shown that modafinil can be rewarding under certain conditions. The present study assessed the reinforcing properties of modafinil using conditioned place preference and locomotor sensitization in mice. Experiment 1 examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 48 publications
2
33
3
Order By: Relevance
“…This may be related to the higher nicotine dose used in the P-rats (60 mg/kg/infusion) than that used in the Long-Evans rats (30 mg/kg/infusion). We also note that (±)-MOD produces conditioned place preference (Nguyen et al, 2011;Shuman et al, 2012). However, in this study, R-MOD substitution failed to sustain self-administration in rats previously self-administering nicotine.…”
Section: Discussioncontrasting
confidence: 41%
“…This may be related to the higher nicotine dose used in the P-rats (60 mg/kg/infusion) than that used in the Long-Evans rats (30 mg/kg/infusion). We also note that (±)-MOD produces conditioned place preference (Nguyen et al, 2011;Shuman et al, 2012). However, in this study, R-MOD substitution failed to sustain self-administration in rats previously self-administering nicotine.…”
Section: Discussioncontrasting
confidence: 41%
“…Although it is not at novel concept that exposure to one stimulant may increase the abuse potential for other stimulants (Shuman et al, 2012; Rosine et al, 2009; Valvassori et al, 2007; Tronci et al, 2006; Yang et al, 2003), this paper is particularly relevant when considering previous data on cross sensitization of stimulants. While many groups have previously shown that stimulants do, indeed, produce cross sensitization and cross-tolerance (Shuman et al, 2012; Rosine et al, 2009; Valvassori et al, 2007; Tronci et al, 2006; Yang et al, 2003; Ferris et al, 2012, 2013a; Calipari et al, 2013c), here we expand and clarify this idea.…”
Section: Discussionmentioning
confidence: 99%
“…was not reinforcing when administered alone (Deroche-Gamonet et al, 2002); however, we have recently found that modafinil (75 mg/kg i.p.) alone can produce a conditioned place preference (Shuman et al, 2012), indicating that modafinil is at least a weak reinforcer. Indeed, administration of modafinil (800 mg, roughly 10 mg/kg p.o.)…”
Section: Modafinilmentioning
confidence: 99%